MANAJEMEN RISIKO KELEMBAGAAN PENDIDIKAN ISLAM BERBASIS PRINSIP IKHTIAR DAN TAWAKKAL - Muhammad Fauzi Ridwan; Muhammad Riff'an Alghiffari; Rodotul Jannah (Universitas Islam Bunga Bangsa Cirebon, 2022)
Institutional risk management in Islamic educational institutions faces the dual challenge of navigating modern organizational uncertainties while adhering to Islamic theological principles. This study examines the conceptual and practical integration of ikhtiar (earnest effort) and tawakkal (complete reliance on God) as foundational principles in managing institutional risks within Islamic educational organizations. The objective of this research is to construct a comprehensive theoretical framework that synthesizes contemporary risk management models with the aforementioned Islamic principles, thereby offering a contextually relevant approach for madrasah and pesantren administrators. Employing a systematic library research methodology, this study analyzed peer-reviewed academic sources, authoritative Islamic scholarly works, and reputable institutional management texts published within the last five years. Findings reveal that the integration of ikhtiar and tawakkal does not contradict rational risk management practices; rather, it enriches strategic planning, stakeholder engagement, and organizational resilience. Institutions that operationalize these principles demonstrate greater adaptive capacity, ethical governance, and community trust. This framework offers practical implications for policymakers, school principals, and educational managers seeking to strengthen governance quality in Islamic educational settings.